2015
DOI: 10.1177/0731684415617537
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mesoscopic pore size in 3D-interlock fabrics and validation of a predictive permeability model

Abstract: This paper reports an experimental investigation aiming to validate a predictive model of in-plane and transverse permeability for three-dimensional interlock fabrics as a function of fabric architecture. Composite specimens were fabricated and cut to conduct microscopic observations of pore dimensions for five three-dimensional interlock fabrics compressed to a fiber volume content of 58%. The pore cross-section height and width, the number of pores and the pore tortuosity were measured to evaluate an average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…In order to predict the permeability of 2.5 D interlock fabrics , Vernet and Trochu [71,72] developed an analytical model that calculates the pressure drop inside the fabric after predicting the size and distribution of the mesopores. Good agreement was observed at a selected fiber volume fraction for each fabric.…”
Section: Developed Analytical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to predict the permeability of 2.5 D interlock fabrics , Vernet and Trochu [71,72] developed an analytical model that calculates the pressure drop inside the fabric after predicting the size and distribution of the mesopores. Good agreement was observed at a selected fiber volume fraction for each fabric.…”
Section: Developed Analytical Modelmentioning
confidence: 99%
“…Finite element methods are used in a large number of articles [68][69][70][71][72][73][74][75][76][77][78][79]. The approach consists of discretizing the unit cell into elements, inside which reference elements are defined.…”
Section: Review Of Fabric Permeability Prediction: Numerical Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen [14] used a dual-scale model to predict the fabric permeability, and the results showed that the permeabilities of fabrics with the same fiber volume fractions were not necessarily the same. Investigators [15,16,17,18] have established theoretical models to predict the permeabilities of three-dimensional orthogonal and angle-interlock woven fabrics and provided experimental validation of these models. However, the effect of shear deformation on the fabric permeability was not considered in the studies mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…8 modeled the shapes and positions of the pores in unidirectional reinforcements and calculated permeability using a microporomechanical approach. Vernet and Trochu 9 analyzed cross-sectional images obtained by microscopy to determine the pore size distribution, the number of pores, and the tortuosity along different directions of 3D interlock fabrics. These data were then used to validate a predictive permeability model developed previously.…”
Section: Introductionmentioning
confidence: 99%